Integrasi Psikologi Positif dalam Pendidikan - Rahman, Basuki; Hidayat, Ahmad Dirgahayu (CV. Global Cendekia Inti, 2025)
his article aims to examine the integration of positive psychology into education through a literature review, with the goal of understanding its contribution to enhancing learning quality and student well-being. Positive psychology is viewed as a new paradigm that emphasizes the development of strengths, happiness, and resilience, positioning education not solely as a means to achieve academic success but also as a process for fostering character and mental health. The study employs a systematic literature review method by analyzing various relevant primary and secondary sources. The analysis focuses on the core concepts of positive psychology, its application in educational settings, the benefits it brings, as well as the challenges and opportunities related to its implementation across diverse contexts. The findings suggest that integrating positive psychology yields a range of benefits, including increased learning motivation, student engagement, mental well-being, prosocial behavior, and academic achievement. This approach also helps cultivate an inclusive school climate and strengthens students' sense of connection to their learning environment. However, implementation still faces several challenges, such as the dominance of academic achievement-oriented approaches, limited teacher understanding, and the lack of longitudinal research. The article concludes that positive psychology holds significant potential to be integrated into education systems—particularly through curriculum design, character development programs, and the use of digital technology. With systematic and context-sensitive strategies, positive psychology can serve as a critical foundation for building a holistic, balanced, and happiness-oriented educational model that promotes student well-being.